Global impacts of targeted interventions in food security crops – the case of potatoes in developing countries - Kleinwechter, U. (2012)
The present study takes into account the role of potatoes in the global food system and seeks to contribute to the current discussion on agricultural research for food security. To this end, an updated and rebuilt version of the IMPACT-WATER model (Rosegrant et al., 2008) is applied to assess the global impacts of targeted interventions in potato productivity. The calculations of the CGIAR (2011) are taken as a benchmark and a productivity shock of annual potato yield growth which is by 0.5% higher than the baseline growth rates is applied to 30 developing countries, which, based on combined indicators of potato production and livelihoods, have been identified by the International Potato Center (CIP) as priority regions for potato research (Thiele et al., 2010).